2010
DOI: 10.1038/nature08994
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II contributes to cell-scale actin network treadmilling through network disassembly

Abstract: Crawling locomotion of eukaryotic cells is achieved by a process dependent on the actin cytoskeleton1: protrusion of the leading edge requires assembly of a network of actin filaments2, which must be disassembled at the cell rear for sustained motility. Although ADF/cofilin proteins have been shown to contribute to actin disassembly3, it is not clear how activity of these locally acting proteins could be coordinated over the whole-cell distance scale. Here we show that nonmuscle myosin II plays a direct role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
348
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(400 citation statements)
references
References 29 publications
42
348
1
1
Order By: Relevance
“…2 D-E, Movie S1). Similar flow patterns were observed in whole keratocytes, with the important difference that in whole-cells a myosin II-dependent inward actin flow was prominent near the rear boundary (7,16). This difference is likely due to the higher quantity of myosin II in cells (9) compared to fragments (13), which are typically generated from lamellipodia that are relatively poor in myosin (9).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…2 D-E, Movie S1). Similar flow patterns were observed in whole keratocytes, with the important difference that in whole-cells a myosin II-dependent inward actin flow was prominent near the rear boundary (7,16). This difference is likely due to the higher quantity of myosin II in cells (9) compared to fragments (13), which are typically generated from lamellipodia that are relatively poor in myosin (9).…”
Section: Resultssupporting
confidence: 53%
“…Myosin contraction can contribute to rear retraction as well as promote motility by enhancing actin disassembly (7) and inducing forward directed fluid flow (27). However, it is not required; knockouts and inhibition experiments have shown that although myosin II typically promotes movement and increases cell speed, it is not essential for motility in many cell types including keratocytes (5,7,27), Acanthamoeba (28), and Dictyostelium discoideum (29). Here we show that myosin II has a negligible role in rear retraction in keratocyte fragments (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of myosin II also caused a mild, although statistically significant reduction in GzmA-mediated death. Given the role of myosin II in regulating actin dynamics in migrating cells, 27 we hypothesise that myosin may also influence the function of the actin network during athetosis. We also discovered that a high proportion of cells undergoing GzmA-mediated alternate death had altered MTOC localisation; however, microtubule-disrupting agents had no effect, indicating that the actin cytoskeleton has the more critical role.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent in vitro study of actin networks bundled with fascin showed that myosin could spontaneously disassemble contractile structures (40). There may be an interplay between myosin force production and force-induced dissociation of cross-link proteins that controls the lifetime of cellular contractile structures (52,53). Finally, assembly of cellular actomyosin condensates into ordered structures such as contractile rings depends not only on myosin contractility but also on forces produced by actin disassembly (23,54).…”
Section: Discussionmentioning
confidence: 99%